Policy Implication of the Rate of Return Criterion in Higher Educational Investment Planning : The Case of Bangladesh (Bangladesh Journal of Public Administration, 2021)
Financing educational programmes in Less Developed Countries (LDCs) is at the cross-roads. The clamour for socialization of higher education in the face of large number of uncmployeci university graduates vis-a-vis dearth of adequate manpower to feed the development aciivities deserves consideration in a clearer perspectivc. The relatively high incidence of unemployment points out thc econotnic waste involved in using scarce resource. Moreover, for each occupation there is an optimum amount of formal schooling. Thus in some cases, labour productivity declines as schooling increases.